Eco-efficient industrial waste recycling for the manufacturing of fibre reinforced innovative geopolymer mortars: Integrated waste management and green product development through LCA. (20th August 2021) - Colangelo, Francesco; Farina, Ilenia; Travaglioni, Marta; Salzano, Cinzia; Cioffi, Raffaele; Petrillo, Antonella
Abstract: The aim of this research is to evaluate the possibility of using an eco-sustainable geopolymer binder, through the development of innovative technologies capable of offering tools for the water systems management, for the enhancement and protection of environmental resources. Specifically, a hydraulic pipeline made of geopolymer mortar has been designed as prototype. A detailed comparative environmental assessment analysis of unreinforced and reinforced geopolymer prototypes has been conducted using the Life Cycle Assessment (LCA). The LCA study has been performed to determine the environmental performance of the different mix designs and to identify the most important factors contributing to their environmental burdens. The results of the analysis indicate that the advantages of geopolymers make them a valid alternative to traditional binders in many industrial environments and in this case in the realization of useful artifacts for hydraulic engineering.